Predictors of methamphetamine use in disadvantaged neighbourhoods in Czechia - Petruželka, Benjamin; Kupka, Petr; Walach, Václav (Central European Journal of Public Health, 2022)
OBJECTIVE: This study aims to identify predictors of the lifetime prevalence of methamphetamine use in the population of Czech disadvantaged neighbourhoods. METHODS: Using data from a face-to-face representative survey, two types of analysis were performed. A bivariate analysis (unadjusted odds ratios estimated with logistic regression) was conducted to determine the relationship with a dependent variable (lifetime prevalence of methamphetamine use). Subsequently, three multivariate binomial logistic regression models (socio-demographic and socioeconomic status, incarceration and victimization, mobility and space) were conducted to control for the influence of other variables. RESULTS: In a series of multinomial logit models, we have found the following predictors to be significantly associated with lifetime prevalence of methamphetamine use: age, gender, Roma ethnicity, net monthly household income, unstable housing, lifetime experience with incarceration, lifetime experience with discrimination, urban-rural divide, and index of rural peripheralization. CONCLUSIONS: The results suggest that methamphetamine users are multidimensionally disadvantaged and therefore constitute a vulnerable group with specific needs. This should be considered when designing services and policies targeting methamphetamine use in disadvantaged neighbourhoods.
Keywords: socioekonomické faktory; Humans; lidé; Česká republika; logistické modely; bydlení; průzkumy a dotazníky; Socioeconomic Factors; Methamphetamine; Surveys and Questionnaires; Logistic Models; Housing; methamfetamin; Czech Republic